Yeasts from an oligotrophic lake in Patagonia (Argentina): diversity, distribution and synthesis of photoprotective compounds and extracellular enzymes - Brandão, Luciana R. (2011)
Nahuel Huapi (NH) Lake is an oligotrophic temperate lake of glacial origin with high transparency, surrounded by well-developed forests and located at San Carlos de Bariloche, Nahuel Huapi National Park, in Patagonia, Argentina. In this lake, we characterized yeast distribution and diversity along a south-to-north transect and established a relationship between the ability to produce photoprotective compounds (PPCs) (carotenoid pigments and mycosporines) and the occurrence of yeast at different collection points. Subsurface water samples were filtered for yeast isolation. Total yeast counts ranged between 22 and 141 CFU L1, and the highest values corresponded to the most impacted sites. Littoral sites had a low proportion of yeast-producing PPCs and this group prevailed in pelagic sites. This is probably a result of the high transparency of the water and the increased UVexposure. The yeast community from NH Lake showed a high species richness and a uniform distribution of taxa between pelagic and border collection points. Yeasts were identified as belonging to 14 genera and 34 species. Rhodotorula mucilaginosa and Cryptococcus victoriae were the most frequently found species, representing 14.4% and 13.6% of the total yeast isolates, respectively. Most of the yeast isolates demonstrated at least one extracellular enzymatic activity (mainly cellulase and lipase activities), which suggested that these microorganisms are metabolically active in the lake.